2018
DOI: 10.3390/catal8110511
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Eversa Lipase on Octyl Agarose Beads and Preliminary Characterization of Stability and Activity Features

Abstract: Eversa is an enzyme recently launched by Novozymes to be used in a free form as biocatalyst in biodiesel production. This paper shows for first time the immobilization of Eversa (a commercial lipase) on octyl and aminated agarose beads and the comparison of the enzyme properties to those of the most used lipase, the isoform B from Candida antarctica (CALB) immobilized on octyl agarose beads. Immobilization on octyl and aminated supports of Eversa has not had a significant effect on enzyme activity versus p-nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 83 publications
(123 reference statements)
2
36
1
Order By: Relevance
“…However, it seems that the stabilized open form of the lipase exhibited after lipase immobilization on hydrophoboic supports causes this enzyme to be specially sensitive to the negative effects of phosphate anions and to the positive effect of some cations (Ca 2+ and Mg 2+ ) on enzyme stability (Arana-Peña et al, 2018;Cipolatti et al, 2018;Fernandez-Lopez et al, 2015, 2016Zaak et al, 2017b).…”
Section: Advantages Of the Lipase Immobilization On Hydrophobic Supportsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it seems that the stabilized open form of the lipase exhibited after lipase immobilization on hydrophoboic supports causes this enzyme to be specially sensitive to the negative effects of phosphate anions and to the positive effect of some cations (Ca 2+ and Mg 2+ ) on enzyme stability (Arana-Peña et al, 2018;Cipolatti et al, 2018;Fernandez-Lopez et al, 2015, 2016Zaak et al, 2017b).…”
Section: Advantages Of the Lipase Immobilization On Hydrophobic Supportsmentioning
confidence: 99%
“…This causes that in most instances, multipoint immobilized lipase biocatalysts are more stable in aqueous/organic solvents than the just interfacially activated enzyme on hydrophobic supports (dos Santos et al, 2015e, 2015d). Even ionically exchanged lipases may become more stable than the interfacially activated enzymes in these systems (Arana-Peña et al, 2018). It should be remarked that this problem is mainly related to systems consisting of aqueous medium containing high concentrations of organic cosolvent miscible with water,…”
Section: Problems Of Lipase Immobilization On Hydrophobic Supportsmentioning
confidence: 99%
“…The use of high ionic strength should have the contrary effect, favoring the closed form of the lipase but making the adsorption stronger. Ca 2+ has been also used, as it can stabilize some lipases immobilized on these supports (Fernandez-Lopez et al, 2015Arana-Peña et al, 2018;Cipolatti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, phosphate anions have been described to have a very significant destabilizing effect on lipases immobilized on these supports (Zaak et al, 2017a;Arana-Peña et al, 2018), including PFL (Rios et al, 2019c). Comparing two enzyme loads, it may be possible to determine if the enzyme-enzyme interactions can alter the effect of the immobilization conditions on the biocatalysts performance.…”
Section: Introductionmentioning
confidence: 99%
“…An optimized procedure of fluorescein diacetate hydrolysis for quantifying total enzymatic activity in the whole biofilm on the carrier without disturbing immobilization was reported by Dzionek et al, which can serve as a promising method to evaluate the physiological state of immobilized bacterial cells [8]. Additionally, Arana-Peña et al reported the immobilization of Eversa lipase on octyl and aminated agarose beads for the first time, which greatly enhanced the stability of the enzyme [9]. The immobilized enzymes prepared by the cross-linked enzyme aggregates (CLEA) have become more attractive due to their simple preparation and high catalytic efficiency.…”
mentioning
confidence: 99%